PENGARUH PROCUREMENT PLANNING DAN KOMPETENSI SDM TERHADAP KINERJA PENGADAAN BARANG/JASA PT ANGKASA PURA I (PERSERO) MELALUI E-PROCUREMENT SYSTEM DENGAN INFORMATION TECHNOLOGY SEBAGAI VARIABEL MODERATOR - Gabby Pinaria, Astried; Supriyadi, Edy; Derriawan (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
Astried Gabby Pinaria1, Edy Supriyadi2, Derriawan3 Angkasa Pura 1,Sekolah Pascasarjana Universitas Pancasila23 e-mail: astriedpinaria88@gmail.com ABSTRACT The study aims to determine whether there is an influence of procurement planning and HR competencies on the performance of goods / services procurement of PT Angkasa Pura I (Persero) through the implementation of e-procurement system with moderation of Information Technology in the process of procurement of goods / services at the Head Office of PT. Angkasa Pura I (Persero). The method used in this study is a descriptive statistical method with quantitative through questionnaire survey and observation approaches in the field, where the research sample is the Procurement Unit, Technical Unit and Goods / Services Provider at the Head Office of PT. Angkasa Pura I (Persero). To test this hypothesis Structural Equation Model (SEM) - PLS and using WarpPLS 7.0 tools from the results of the research conducted, an analysis was produced that showed that procurement planning has a significant effect on e-procurement systems, and HR competence has a significant effect on e-procurement system, procurement planning has a significant effect on the performance of goods / services procurement through e-procurement system, HR competence has a significant effect on the performance of goods / services procurement through e-procurement system but the direct effect is not significant on the performance of goods / services procurement, e-procurement system significant effect on the performance of procurement of goods / services and there is a significant influence between the interaction of e-procurement systems on the performance of procurement of goods / services that are moderated by information technology